2020
DOI: 10.3390/math8111951
|View full text |Cite
|
Sign up to set email alerts
|

Who Knocks on the Door of Portfolio Performance Heaven: Sinner or Saint Investors?

Abstract: To sin, or not to sin: that has been the question for many people for a long time, and nowadays that question has moved to the financial markets. The existence of studies that show that investing in vice sectors such as the alcohol, tobacco, and gambling industries, collectively known as the “triumvirate of Sin”, is profitable has created some uncertainty for investors who wonder whether or not to be socially responsible. We show that by implementing an investment strategy based on the Fama–French five-factor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…Nonetheless, various empirical studies comparing ESG and non-ESG portfolio performance have yielded contradictory results. An increasing number of studies (Cesarone et al , 2022; Beloskar and Rao, 2022; Badía et al , 2021; Bermejo Climent et al , 2021; Yook and Hooke, 2020; Miralles-Quirós and Miralles-Quirós, 2020; Wu et al , 2017; Tripathi and Bhandari, 2015; Kempf and Osthoff, 2007; Derwall et al , 2005; Statman, 2005) have found that ESG portfolios engendered superior performance compared with non-ESG portfolios. On the contrary, several research studies (Milonas et al , 2022; Torre et al , 2020; Hartzmark and Sussman, 2019; Ur Rehman et al , 2016; Ortas et al , 2014; Guenster, 2012; Young and Proffitt, 2003; Hamilton et al , 1993) have concluded that ESG portfolios either underperform non-ESG portfolios or there is no statistically significant difference between the two.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, various empirical studies comparing ESG and non-ESG portfolio performance have yielded contradictory results. An increasing number of studies (Cesarone et al , 2022; Beloskar and Rao, 2022; Badía et al , 2021; Bermejo Climent et al , 2021; Yook and Hooke, 2020; Miralles-Quirós and Miralles-Quirós, 2020; Wu et al , 2017; Tripathi and Bhandari, 2015; Kempf and Osthoff, 2007; Derwall et al , 2005; Statman, 2005) have found that ESG portfolios engendered superior performance compared with non-ESG portfolios. On the contrary, several research studies (Milonas et al , 2022; Torre et al , 2020; Hartzmark and Sussman, 2019; Ur Rehman et al , 2016; Ortas et al , 2014; Guenster, 2012; Young and Proffitt, 2003; Hamilton et al , 1993) have concluded that ESG portfolios either underperform non-ESG portfolios or there is no statistically significant difference between the two.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…Hartzmark and Sussman (2019) find no evidence that high-sustainability funds outperform low-sustainability funds. When compared to the initial stock–bond portfolio, Miralles-Quirós and Miralles-Quirós (2020) discovered that investment in exchange traded funds (ETFs) that contribute to the SDGs can result in substantial gains in portfolio performance. The fossil-free portfolio lagged the traditional stock portfolio in the early years, but this trend reversed in the subsequent years (Yook and Hooke, 2020).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…Meanwhile, sustainable investment is a broad concept that covers other more specific types of investment such as the so-called impact investment, that combines financial objectives with social ones (labour and human rights, among others). Nevertheless, we have to highlight so-called green investment, which considers environmental objectives (environmental policies, external/internal management systems, climate change indicators, emissions, solid waste, water, among others) in addition to financial ones [12]. This type of investment has attracted the attention not only of investors but also of all stock market participants.…”
Section: Introductionmentioning
confidence: 99%